What Should We Do When HIV-positive Children Fail First-line Combination Antiretroviral Therapy? A Comparison of 4 ART Management Strategies. Issue 4 (April 2019) - Patten, Gabriela; Schomaker, Michael; Davies, Mary-Ann; Rabie, Helena; van Zyl, Gert; Technau, Karl; Eley, Brian; Boulle, Andrew; Van Dyke, Russell B.; Patel, Kunjal; Sipambo, Nosisa; Wood, Robin; et al.
Abstract : Background: Managing virologic failure (VF) in HIV-infected children is especially difficult in resource-limited settings, given limited availability of alternative drugs, concerns around adherence, and the development of HIV resistance mutations. We aimed to evaluate 4 management strategies for children following their first episode of VF by comparing their immunologic and virologic outcomes. Methods: We included children (< 16 years of age) with VF from 8 International Epidemiologic Database to Evaluate AIDS Southern Africa cohorts, initiating combination antiretroviral therapy (cART) between 2004 and 2010, who followed one of the 4 management strategies: continuing on their failing regimen; switching to a second-line regimen; switching to a holding regimen (either lamivudine monotherapy or other non-cART regimen); discontinuing all ART. We compared the effect of management strategy on the 52-week change in CD4% and log10 VL from VF, using inverse probability weighting of marginal structural linear models. Results: Nine hundred eighty-two patients were followed over 54, 168 weeks. Relative to remaining on a failing regimen, switching to second-line showed improved immunologic and virologic responses 52 weeks after VF with gains in CD4% of 1.5% (95% confidence interval [CI], 0.2–2.8) and declines in log10 VL of -1.4 copies/mL (95% CI, -2.0, -0.8), while switching to holding regimens or discontinuing treatment had worse immunologic (-5.4% (95% CI, -12.1, 1.3) and -5.6% (95% CI, -15.4, 4.1) and virologic outcomes (0.2 (95% CI, -3.6, 4.1) and 0.8 (95% CI, -0.6, 2.1), respectively. Conclusions: The results provide useful guidance for managing children with VF. Consideration should be given to switching children failing first-line cART to second-line, given the improved virologic and immune responses when compared with other strategies. Abstract : Supplemental Digital Content is available in the text.